Charakterystyka zużycia wody w systemach wodociągowych "Turów" i "Serby" w gminie Głogów = Characteristics of water consumption in water supply systems "Turów" and "Serby" in Głogów commune - Ogiołda, Ewa; Nowogoński, Ireneusz; Kłonowska, Renata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Water consumption and its irregularity is an important parameter characterizing water supply system. On the base of values measured during 10 years exploitation in 2 systems water consumption rate and water consumption hour and day irregularity coefficients were calculated and compared with literature and other results.
Keywords: system zaopatrzenia w wodę; zapotrzebowanie na wodę; zużycie wody; water supply system; water demand; water consumption